Correlation between SPT-N and shear wave velocity (VS) and seismic site classification for Amaravati city, India - Kumar, Aakash; Satyannarayana, R.; Rajesh, B. Giridhar (Journal of applied geophysics, 2022)
The present study proposes a set of correlations between standard penetration number (SPT-N) and shear wave velocity (VS) using nonlinear regression analysis. These correlations have been developed for different categories of soil for Amaravati city. This study area is the current de facto seat of government of the Indian state of Andhra Pradesh, India. For this study, SPT-N data has been obtained from 400 boreholes distributed across the city of area 217.23 km2. Most of the boreholes considered for this study have a boring depth of 25 m to 45 m below the recorded ground surface. A comparison between the proposed correlations with existing worldwide accepted correlations has been performed to check the authenticity of this study. In addition to this, Vs obtained from the recommended correlations have been validated with the Vs obtained from 30 microtremor tests as well as established graphical methods. Furthermore, the seismic site classification of the study area has been conducted using the developed correlation for all soils. It is observed that the major part of Amaravati city falls under class D as per the National Earthquake Hazard Reduction Program (NEHRP) provisions. The average SPT-N and VS distribution across the city has also been generated at depths of 5, 10, 15, 20, 25, and 30 m. The outcomes of the study can be further used for the design of earthquake-resistant structures, seismic hazard studies, estimation of ground movements, and generation of site-specific synthetic ground motions. •Correlations between SPT-N & shear wave velocity (VS) of soils for Amaravati city.•Validation of proposed correlations with microtremor measurements.•Seismic site classification based on SPT-N and shear wave velocity (VS).•The major part of Amaravati city falls under class D as per the NEHRP provisions.•The average SPT-N and VS distribution is generated at depths from 5 m to 30 m.